Serum uric acid is related to liver and kidney disease and 12-year mortality risk after myocardial infarction - Heerkens, Luc; van Westing, Anniek C.; Voortman, Trudy; Kardys, Isabella; Boersma, Eric; Geleijnse, Johanna M. (Frontiers in Endocrinology, 2023)
Objective To study the associations of non-alcoholic fatty liver disease (NAFLD), chronic kidney disease (CKD), and serum uric acid (SUA) in patients with post–myocardial infarction (MI) patients, and the relationship of SUA with 12-year mortality risk. Methods We included 3,396 patients (60–80 years old, 78% men) of the Alpha Omega Cohort. Multivariable prevalence ratios (PRs) were obtained for the association of NAFLD [fatty liver index (FLI), ≥77 (women) and ≥79 (men)] with CKD [estimated glomerular filtration rate (eGFR), <60 mL/min per 1.73 m2]. We calculated sensitivity and specificity of SUA to detect the (combined) presence and absence of NAFLD and CKD. Cause-specific mortality was monitored from enrolment (2002–2006) through December 2018. Hazard ratios (HRs) for all-cause and cardiovascular disease (CVD) mortality in SUA categories were obtained from multivariable Cox models. Results Median baseline FLI was 67 (men, 68; women, 64), and mean ± SD eGFR was 81 ± 20 mL/min per 1.73 m2 (17% with CKD). Sex-specific FLI was associated with higher CKD prevalence (PRtertile3 vs. tertile1, 1.94; 95% confidence interval: 1.57, 2.39). Baseline SUA was 0.36 ± 0.09 mmol/L. With increasing SUA concentrations, specificity for the presence of NAFLD, CKD, or both increased, and sensitivity decreased. During 12 (interquartile range, 9–14) years of follow-up, 1,592 patients died (713 from CVD). HRs ranged from 1.08 (0.88, 1.32) for SUA ≤0.25 mmol/L to 2.13 (1.75, 2.60) for SUA >0.50 mmol/L vs. SUA >0.30–0.35 mmol/L for all-cause mortality. For CVD mortality, HRs ranged from 1.05 (0.77, 1.44) to 2.43 (1.83, 3.25). Conclusions NAFLD and CKD were strongly associated, which was reflected by higher SUA concentrations. SUA was a strong predictor of 12-year mortality risk after MI.